Visualisasi Pemahaman Hadis dalam Serial Animasi; Studi Kasus Nusa-Rara - Siradjudin Abdul Faraj; Sandi Sentosa; Bustamin (Departement of Hadith Sciences, Faculty of Ushuluddin, UIN Syarif Hidayatullah, Jakarta, 2025)
This article examines how the popular Indonesian Islamic children's animation Nussa & Rara visualizes the meaning of prophetic traditions (hadith) and assesses whether these visualizations conform to the established understanding of hadith scholars. As Islamic discourse increasingly migrates to the virtual world—where religious authority shifts from scholarly competence to digital popularity—children's animation becomes a significant yet under-examined vehicle for transmitting hadith to an audience that cannot yet distinguish authentic from fabricated traditions. Using a qualitative library-research design, the study identifies seven episodes in Season Two containing hadith citations (only 22% of 31 episodes), performs takhrīj al-ḥadīth on each using Wensinck's al-Muʿjam al-Mufahras, and analyzes their visualization through Roland Barthes's semiotic theory of lexia and his five reading codes. The findings show that five of the seven hadiths are ṣaḥīḥ and two are ḥasan; none are weak or fabricated. In six of seven episodes, the visualization conforms to classical scholarly commentary (al-Nawawī, Ibn Ḥajar, al-Maqdisī, al-Mubārakfūrī). In one episode, the visualization diverges: the hadith